Studi Ketersedian Sarana dan Prasarana Perumahan Graha Youtefa di Kelurahan Waena Kota Jayapura - Yoseph Aitrem; Deasy Widyastomo; Tommi Tommi; Monita Yessy Beatrick; Juliani Wairata (Fakultas Teknik Universitas Cenderawasih, 2024)
Fulfilling the need for housing, the suitability of the existing conditions of housing infrastructure in Waena Village, Heram District, Jayapura City need to be considered in order to meet certain standards for the need for a decent, healthy, safe and comfortable place to live. The methods used in research are survey methods and case methods (case studies). The type of research used is quantitative and descriptive qualitative research. Meanwhile, the quantitative approach results from the public's perception that the condition of the availability of facilities and infrastructure at the Graha Youtefa Housing Complex is >40-70%